International Trade and Developing Countries: Bargaining coalitions in the GATT & WTO - Narlikar, Amrita (RIPE Series in Global Political Economy, 2003)
A keen analysis of how and why countries bargain together in groups in world affairs, and why such coalitions are crucial to individual developing nations. It also reveals the effects these negotiating blocs are having on world affairs. Successful coalition building has proven to be a difficult and expensive process. Allies are often not obvious and need to be carefully identified. Large numbers do not necessarily entail a proportionate increase in influence. And the weak have the choice of teaming up against or jumping on the bandwagon with the strong. Even after it has been organised, collective action entails costs of many kinds. This book investigates the relevance and workability of coalitions as instruments of bargaining power for the weak. More specifically, this analyzes the coalition strategies of developing countries at the inter-state level, particularly in the context of international trade. Given the nature of this enquiry, this new study uses theoretical and empirical methods to complement each other. The theoretical approach draws from a plethora of writings: formal theories of clubs and coalitions, theories of domestic political economy and theories of international relations. The empirical analysis of comparable coalitions becomes necessary to assist in this theorising, so the greater part of the book focuses mainly (though not exclusively) on coalitions involving developing countries on the issue-area of trade in services. Through the case-studies of the Uruguay Round and an analytical overview of more recent coalitions, this text fills an important gap in the literature of international political economy and international relations where most GATT/WTO-based coalitions have eluded record. This book will be of great interest to all students of international relations, politics and globalization.